CRIMINAL LIABILITY OF ONLINE FRAUD PERPETRATORS THROUGH ILLEGAL ONLINE LOAN APPLICATIONS - Okprianti, Reny; Emilson, Nur Husni; Rafli, Muhammad; Prattiwy, Amanda; Octavia, Wanda Puja; Zerlinda, Frity Vania (JILPR Journal Indonesia Law and Policy Review, 2025)
The rapid development of technology has had an impact on changes in people's lifestyles, where things can be done quickly and easily using online-based services or using the internet network, whether in terms of shopping transactions, booking hotels, paying electricity bills, train tickets, plane tickets, or making money or capital loan transactions online. The method used is normative legal research with a library research approach, which examines literature, laws and regulations, and relevant legal documents. The results of the study show two main findings. First, illegal online loan providers can be held accountable civilly, criminally, and administratively. In the civil realm, they are required to compensate for losses based on Article 1365 of the Civil Code. In the criminal realm, perpetrators can be charged with articles related to extortion, misuse of personal data, and fraud. Meanwhile, administratively, the OJK has the authority to impose sanctions such as license revocation and access blocking based on POJK No. 77/POJK.01/2016. Second, delinquent debtors who utilize illegal online loans to commit fraud, such as identity falsification or fictitious loans, can be charged with Article 378 of the Criminal Code if there is evidence of malicious intent. The implications of this research are the need to increase public awareness of the right to personal data privacy, strengthen law enforcement, and update policies in accordance with the dynamics of the digital era.